2015
DOI: 10.1016/j.bbamem.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide dendrimer interacts with phosphocholine membranes in a fluidity dependent manner: A neutron reflection study combined with molecular dynamics simulations

Abstract: The interaction mechanism of a novel amphiphilic antimicrobial peptide dendrimer, BALY, with model lipid bilayers was explored through a combination of neutron reflection and molecular dynamics simulations. 1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and 1,2-dipalmitoyl-sn-glycero-3-phos-phocholine (DPPC) lipid bilayers were examined at room temperature to extract information on the interaction of BALY with fluid and gel phases, respectively. Furthermore, a 1:4 mixture of POPC and DPPC was used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Our NR data shows that SLBs formed via vesicle fusion from total E . coli lipid extracts present high coverage and structural features similar to fluid phosphatidylcholine membranes made from lipids with 16:0 acyl chains (fluid DPPC; tail: 28 ± 1, head: 7 ± 1 Å [ 39 , 61 ]). The typical chain lengths of the E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our NR data shows that SLBs formed via vesicle fusion from total E . coli lipid extracts present high coverage and structural features similar to fluid phosphatidylcholine membranes made from lipids with 16:0 acyl chains (fluid DPPC; tail: 28 ± 1, head: 7 ± 1 Å [ 39 , 61 ]). The typical chain lengths of the E .…”
Section: Discussionmentioning
confidence: 99%
“…The reconstituted membranes are slightly thinner than supported lipid membranes based on phosphatidylcholine membranes with 16:0–18:1 acyl chains (1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine (POPC), tail: 31 ± 1 Å, head 8 ± 1 Å) as measured by neutron reflection. [ 52 , 61 ] PE lipids are known to increase the chain order of lipid mixtures and thus slightly increase the hydrophobic thickness (by 1 Å) of lipid bilayers. [ 31 ] However, this effect could be counteracted by the presence of cyclic species that decrease the chain order.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed the optimal growth temperature for macrophages used in the experiments cited above is 37°C, while these experiments have been conducted at 32°C to mimic the optimal growth temperature of M. ulcerans (131). Using a suboptimal temperature can affect the antimicrobial activities of macrophages, such as cytokine production, antimicrobial peptide secretion, and activities and membrane dynamics required for phagolysosome biogenesis (132)(133)(134). Under these conditions, the survival and the multiplication of M. ulcerans cells in macrophages are facilitated.…”
Section: Cellular and Animal Models For M Ulcerans Infectionmentioning
confidence: 99%
“…NR also allows to simultaneously resolve potential lipid removal as well as peptide insertion into partly deuterated supported lipid bilayers (SLBs). [31][32][33][34][35][36][37][38] In an earlier work, we showed that NR results can be directly compared to results from detailed modelling of small angle X-ray scattering (SAXS) data on monomeric peptide lipid bilayer using SLBs or unilamellar vesicles respectively. 31 For supramolecular nanobers in particular, NR has an advantage over bulk methods since it lacks 3D orientation averaging and enables precise structural determination of complex MDP-membrane structures.…”
Section: Introductionmentioning
confidence: 99%